2016
DOI: 10.1159/000453210
|View full text |Cite
|
Sign up to set email alerts
|

H2S Attenuates LPS-Induced Acute Lung Injury by Reducing Oxidative/Nitrative Stress and Inflammation

Abstract: Background: Hydrogen sulfide (H2S), known as the third endogenous gaseous transmitter, has received increasing attention because of its diverse effects, including angiogenesis, vascular relaxation and myocardial protection.We aimed to investigate the role of H2S in oxidative/nitrative stress and inflammation in acute lung injury (ALI) induced by endotoxemia. Methods: Male ICR mice were divided in six groups: (1) Control group; (2) GYY4137treatment group; (3) L-NAME treatment group; (4) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 47 publications
14
80
0
2
Order By: Relevance
“…We firstly investigated the cyto-protective effect of NaHS on EPCs isolated from peripheral blood of healthy donors in vitro , and it showed that 500uM NaHS caused a reduction in cell proliferation, which was consistent with the results of Potenza et al [15]. Therefore, we used NaHS with a concentration of 25-200uM in subsequent studies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We firstly investigated the cyto-protective effect of NaHS on EPCs isolated from peripheral blood of healthy donors in vitro , and it showed that 500uM NaHS caused a reduction in cell proliferation, which was consistent with the results of Potenza et al [15]. Therefore, we used NaHS with a concentration of 25-200uM in subsequent studies.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, we used NaHS with a concentration of 25-200uM in subsequent studies. Based on previous report [15], we postulated that the potential mechanism associated with inhibitory effect of 500 uM NaHS might be related to dys-regulation of calcium dependent signaling pathway and cellular toxicity. Importantly, we found that NaHS-preconditioning significantly improved EPCs function with a maximal concentration of 200 uM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Histopathological analysis was performed as previously described [34]. The total area of the vascular walls was quantified with high-resolution images of individual vessels using a color-recognition algorithm in Image-Pro Plus 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…ARDS is characterized by massive inflammatory cell infiltration, increased capillary permeability, severe alveolar damage and the formation of hyaline membranes [3][4][5][6]. The primary insults leading to ARDS include microbial infection, pollutants, toxic gasses, gastric acids, autoantibodies, fatty emboli, free fatty acids and transfusion [7,8].…”
Section: Introductionmentioning
confidence: 99%